MODEL PENANGGULANGAN CARDING - Rofikah., Rofikah (Faculty of Law, Universitas Sebelas Maret, 2014)
This study issue was the credit card crime (carding) in Indonesia conductedin Bank Indonesia and Indonesian National Police Headquarters. Carding is international cyber crime causing society restively particularly the credit card users, due to the computer technology of carding beyond the national boundary. The coordinated, inter-state cooperation and understanding of science and mastery of computer and related products are mandatory to the necessity of facing the cyber crime carding. The primary data obtained by direct interviews with the police (Police Headquarters) and Bank Indonesia meanwhile the secondary data attained from books, magazines, internet and research. This study indicated that the handling of carding preventively conducted by the Police in coordination with Bank Indonesia to supervised/ restricted the circulation / issuance of credit cards, issuing red book on carding prevention guideline and actively informed the banking about carding issues. Meanwhile, Bank Indonesia are obliged to form theregulation draftin credit cards utilization Carding.countermeasuresreperesively performed using mediation between the bank that issued the credit card, the credit card holder and carding actors with Bank Indonesia as the mediator. If mediation did not reach an agreement, the cases would be handed over to the police, treated as a crime in general.